Association of MCP‐1 promotor polymorphism with disease severity of Crimean‐Congo hemorrhagic fever. Issue 12 (5th April 2020) - Bagci, Binnur; Bagci, Gokhan; Buyuktuna, Seyit Ali; Elaldi, Nazif
Abstract: Crimean‐Congo hemorrhagic fever (CCHF) is a thick‐borne viral zoonotic disease. The pathogenesis and the reasons why cases have a mild or severe course in CCHF have not yet been explained. In this study, we investigated the relationship between promoter ‐2518 A/G single‐nucleotide polymorphism (SNP) of the MCP‐1 gene and the clinical course of CCHF. The MCP‐1‐2518 A/G SNP (rs1024611) frequency was examined in 128 virologically/serologically confirmed CCHF patients and 181 healthy controls by using the PCR‐RFLP method. When CCHF patients and controls were compared, no significant difference was found between genotype distributions and allele frequencies of the ‐2518 A/G SNP of MCP‐1 gene ( P > .05). Compared to the AA genotype, both AG ( P = .016; OR = 2.57) and GG genotype ( P = .039; OR = 3.43) were found with significantly higher frequencies in mild/moderate cases than in severe cases. Compared to the AG + GG genotype, AA showed a significant risk for severe CCHF (60.0% vs 38.4%, P = .02; OR = 2.41). In contrast, the AG genotype showed a significant protective effect against severe disease compared to AA + GG genotype (29.1% vs 47.9%, P = .013; OR = 2.58). Compared to mild/moderate cases, the A allele was found to be significantly higher in severe cases (0.745 vs 0.623, P = .039; OR = 1.77). However, no significant relationship was found between fatal and nonfatal cases in terms of genotype or allele frequencies ( P > .05). In conclusion, both ‐2518 AA genotype and A allele of MCP‐1 were associated with disease severity, and the AG genotype had a protective effect against a severe disease course in CCHF patients. Research Highlights: AG and GG genotype were found significantly higher frequency inmild/moderate cases than in severe cases.